Analisis Kapasitas Apron dari Aspek Jumlah Pergerakan Penumpang, Jumlah Pergerakan Pesawat dan Waktu Pesawat di Apron pada Sebuah Bandara di Indonesia - Al Ayubbi, Faqih; Pamuraharjo, Hemi; Wardhana, Pramudika Wisnu (LANCAH: Jurnal Inovasi dan Tren, 2024)
Air transport is a type of transport system that is widely used for passengers and cargo, both domestic and international. Indonesia is one of the countries that strongly supports the development of air transport. The growth of air transportation and technological development every year is getting faster, therefore, this research aims to analyse the capacity and optimisation of aprons at airports. The analysis is conducted by identifying the current apron capacity, forecasting future apron requirements, and determining the necessary optimisation measures. This study uses aircraft movement data from 2014 to 2020, and applies the linear regression method to project aircraft movements in 2023 and 2028. Three forecasting scenarios were used to handle outlier data due to events such as ticket fare increases and the COVID-19 pandemic. The analysis results show that the current apron capacity is sufficient, but will exceed capacity in the coming year. Therefore, additional parking stands are recommended as a long-term optimisation measure. This research provides important insights for airport facility development planning to accommodate the continuous increase in air traffic. Thus, the addition of parking stands and other optimisation measures are necessary to maintain the smooth operation of the airport in the future and ensure that the airport facilities can accommodate the increasing air traffic.